KARAKTERISTIK PERUSAHAAN YANG MEMPENGARUHI TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur Non Logam yang terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Lintang Kurniawati; Nur Kholis (Prosiding University Research Colloquium, 2020)
The study aims to determine the effect of the independent variablesnamely company size, sales growth, leverage, capital intensity andindependent commissioners on tax avoidance in non-metalmanufacturing companies listed on the Indonesia Stock Exchange in2016-2018. The total sample of the study was 54 financial statementsof non-metal manufacturing companies which were determined basedon the purposive sampling method. The data collection method usedis the documentation method in the form of financial statements ofnon-metal manufacturing companies listed on the Indonesia StockExchange in 2016-2018. Hypothesis testing using multiple regressionanalysis with the SPSS 21 program and previously tested classicassumption. The results of this study indicate that company size, salesgrowth and capital intensity effect tax avoidance. While leverage andindependent commissioners have no effect on the tax avoidance